Vowel deletion in Raimi and Najdi Arabic - ALAHDAL, A.A (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT Dialectical variations operate at varied linguistic levels giving a dialect its unique place on the language map. In a paper, AlYaari et al. tried to consider a comparative study of the linguistics of the different dialects of Yemeni Arabic DYA. This paper looks at Raimi Yemeni Arabic, a dialect that is not considered by AlYaari et al. The paper considers two phonological phenomena studied by Alyaari et al.; namely, vowel deletion and absence of diphthongs. The paper demonstrates that RA is similar to Adeni Arabic in terms of vowel deletion, but is unique in monophthongization. RESUMEN Las variaciones dialécticas operan en niveles lingüísticos variados que le dan a un dialecto su lugar único en el mapa del idioma. En un artículo, AlYaari trató de considerar un estudio comparativo de la lingüística de los diferentes dialectos del árabe yemení DYA. Este artículo analiza el árabe ramio yemení, un dialecto que AlYaari no consideran. El artículo considera dos fenómenos fonológicos estudiados por Alyaari ; a saber, eliminación de vocales y ausencia de diptongos. El documento demuestra que la AR es similar al árabe Adeni en términos de eliminación de vocales, pero es única en la monoptongación.